Scientist's industry engagement and the research agenda: Evidence from Germany - Florence Blandinieres; Maikel Pellens (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We investigate the impact of industry engagement on the direction of academic science. We apply the framework of the research agenda to assess to which extent industry engagement shifts the costs and benefits of pursuing and adopting research topics. Our empirical analysis, based on a survey of German scientists, shows that scientists who engage more with industry are more likely to incorporate commercial considerations in selecting a research topic, and are less likely select a topic for its potential to contribute to ongoing scientific discussions. They are also more likely to consider industry an important sponsor to explore new research topics. In this way, too much emphasis on engagement might alter the direction of scientific progress towards industrially relevant research areas.
Keywords: I23; O33; 330; Industry-science links; Industry engagement; research agenda